Climate change and the influence of monetary policy in China - Xiaoni Song; Tong Fang (Journal of Applied Economics)
We investigate whether climate change affects the efficiency of monetary policy. We use temperature shocks, calculated as temperature deviations from historical average temperatures, to proxy climate change, and utilize a threshold vector autoregression model (TVAR) to estimate the impact of expansionary and tight monetary shocks on economic output under high and low regimes of temperature shocks. Our results characterize a climate change regime-dependent monetary policy. Expansionary monetary policy is less efficient and the negative impact of tight monetary policy is enhanced, when climate change is severe. The results can be explained by the climate-induced credit constraint of commercial banks. Higher temperature shocks lead to increases in banks’ non-performing loan ratios, which results in larger credit constraints of banks. Banks tend to be more prudent in credit expansion, and the bank credit channel of monetary policy transmissions is weakened.